Analysis of living environment settings in residential areas in Kuala Lumpur and Putrajaya - Kadar Hamsa, Abdul Azeez; Sugaya, Daiki; Miura, Masao (Universitat Politecnica De Catalunya Barcelonatech, 2015)
The rise in population in Malaysia has been exerting tremendous pressure on housing needs and other related physical infrastructure. As a result, residents are subjected to deteriorated living environmental conditions. This paper examines the existing living environmental conditions of the residents in terrace houses, through use of a questionnaire survey. Three old residential areas namely Taman Gombak (TG), Taman Sri Rampai (SR) and Desa Setapak (DS) in Kuala Lumpur city which were built before 1980, and one new residential area at Putrajaya (PP), located outside Kuala Lumpur and built after 2000, were selected. The findings showed that the residents in the old residential areas were dissatisfied with existing living environmental conditions such as level of crime, the bad smell of garbage, and noise levels. Whereas the residents in the new residential area were dissatisfied with the level of conveniences such as regional facilities and traffic networks.